Multipliers of taxes and public spending in Colombia: SVAR and local projections approaches - Sergio Restrepo-Ángel; Hernán Rincón Castro; Juan J. Ospina-Tejeiro (Latin American Journal of Central Banking (LAJCB), 2022)
This paper estimates and analyzes multipliers for tax revenue and public spending for Colombia using structural autoregressive vectors and local projections models. Quarterly series of the central national government between 2000Q1 and 2018Q4 are used. The results show fiscal multipliers that are less than unity when the state of the economy is not considered and a spending multiplier around unity when the economy is in an expansionary phase. The spending multiplier is greater and bigger than one during a contractionary phase, supporting the case for conducting countercyclical fiscal policy in this state. The tax revenue multiplier is negative and much smaller in magnitude than the spending multiplier. The results are robust to different identification schemes and estimation methodologies.
Keywords: C32; C51; C53; E62; 330; Blanchard and Perotti; Fiscal multipliers; Fiscal shocks; Standard and smooth local projections